Capture, Culture and Release of Postlarvae Fishes: Proof-of-Concept as a Tool Approach to Support Reef Management - Cortés-Useche, Camilo; Reyes-Gamboa, Williams; Cabrera-Pérez, José Luís; Calle-Triviño, Johanna; Cerón-Flores, Ana; Raigoza-Figueras, Rodolfo; Yathiraj, Roshni; Arias-González, Jesús Ernesto (Frontiers in Marine Science, 2021)
The changing world presents negative impacts on marine ecosystems and has led to the development of diversified tools to support reef restoration. Harnessing restoration to achieve success needs innovative techniques that also address the restoration of reef fish assemblages, contributing to the conservation of biodiversity and ecosystem functions and also tackle the cost-effectiveness through impact-driven solutions. Here, we propose a proof-of-concept for enhancing fish populations on reefs using: (1) postlarvae capture, (2) aquarium culture, and (3) release to reef sites. We conducted field studies in the Mexican Caribbean to analyze for the first time, the possibility of using the capture and aquarium culture of postlarvae fish species and release of juveniles as a tool for the potential recovery of reef biodiversity resilience. We tested the potential of postlarvae capture using two distinct night light traps (BOX and collect by artificial reef ecofriendly traps, C.A.R.E.) in three sampling sites with different distances from shoreline and depth. We collected 748 postlarvae reef fishes from eight orders, 20 families, and 40 species. Acanthuridae, Pomacentridae, Monacanthidae, and Tetraodontidae comprised the highest species number of postlarvae families. We also set up a pilot release experiment with Stegastes partitus using two trials (32 and 1 day after capture) and propose analysis to determine appropriate reef sites to release the cultured juveniles and to aid ecological planning. We present the results of the pilot release experiment with S. partitus, showing that there is a positive effect in survivorship during the capture (80%) and release (76–100%) procedures into suitable habitat and good chance that more studies will bring novelty to the field. Although trials carried out with more species relevant to restoration will be needed. The use of these techniques can be a great opportunity to improve the research of restoration efforts in the Caribbean region with fish-depleted coral reefs with vulnerable food webs, especially at local scales and supporting other management strategies.